2007
DOI: 10.2172/924162
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Mineral Carbonation: Enhancing Carbonation While Avoiding Mineral Pretreatment Process Cost

Abstract: Known fossil fuel reserves, especially coal, can support global energy demands for centuries to come, if the environmental problems associated with CO 2 emissions can be overcome. Unlike other CO 2 sequestration candidate technologies that propose long-term storage, mineral sequestration provides permanent disposal by forming geologically stable mineral carbonates. Carbonation of the widely occurring mineral olivine (e.g., forsterite, Mg 2 SiO 4 ) is a large-scale sequestration process candidate for regional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Once precipitated, MgCO 3 is a solid at room temperature (solubility in water, 0.0139 g per 100 ml at 25°C) and 0.64 M NaHCO 3 is soluble at room temperature (solubility in water, 10 g per 100 ml at 25 °C). 7,11 Drying the wet sample would add NaHCO 3 to the total inorganic carbon concentration, which could be misleading. Thus, to precisely quantify the MgCO 3 formed, the inorganic carbon for the dried liquid was subtracted from the inorganic carbon for the solid value.…”
Section: Carbonation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once precipitated, MgCO 3 is a solid at room temperature (solubility in water, 0.0139 g per 100 ml at 25°C) and 0.64 M NaHCO 3 is soluble at room temperature (solubility in water, 10 g per 100 ml at 25 °C). 7,11 Drying the wet sample would add NaHCO 3 to the total inorganic carbon concentration, which could be misleading. Thus, to precisely quantify the MgCO 3 formed, the inorganic carbon for the dried liquid was subtracted from the inorganic carbon for the solid value.…”
Section: Carbonation Experimentsmentioning
confidence: 99%
“…4,5 Research efforts on mineral carbonation have focused on efficient mineral activation, determining the optimum conditions for mineral dissolution and precipitation, and enhancing reaction kinetics to maximize conversion. [6][7][8][9][10][11][12][13][14][15] Some of the most abundant minerals on Earth, serpentine (Mg 3 Si 2 O 5 (OH) 4 ) and olivine (MgSiO 4 ) require some form of activation or pretreatment to react. 8,[16][17][18] Pretreatment of serpentine to convert it to olivine involves heating to high temperatures (>610 °C), which is also energy intensive.…”
Section: Introductionmentioning
confidence: 99%
“…8(c)) from the surface of the olivine due to volumetric differences and resulting stresses between the olivine crystal and the layer depleted of Mg and O. 70,98,99 The exfoliation rate depends on the thickness of the passivation layer. The hydrothermal deposition of silica is known to contribute to the irregular surface morphology of the amorphous layer, leading to the formation of brittle silica.…”
Section: Morphological Evolution During Direct Carbon Mineralization ...mentioning
confidence: 99%
“…The influence of chemical additives, including bicarbonate compounds like NaHCO 3 , and organic ligands such as Na 2 H 2 EDTAÁ2H 2 O, have been investigated for their individual effects on carbon mineralization efficiency in direct carbon mineralization studies. 2,8,22,28,30,31,48,[70][71][72][73][74] It has been reported that the addition of 2 M NaHCO 3 significantly enhances the carbon mineralization efficiency by approximately 50-60%. 8,28 Upon dissolution in the aqueous phase, NaHCO 3 dissociates to produce bicarbonate ions (R2).…”
Section: Effect Of Chemical Additives and Mineral Chemistry On Integr...mentioning
confidence: 99%
“…Mg 2+ (aq)+ Ca 2+ (aq) + 2HCO 3 − (aq) = (Ca,Mg)CO 3 (s) + 2H + (aq) (6) Numerous laboratory experiments have been performed to study the reactivity of olivine, serpentine, pyroxene, amphibole and plagioclase mineral groups, and glass basalt lavas with CO 2 -enriched solutions [17][18][19][20]. Most of these experiments were conducted in batch conditions at controlled pressure, temperature and P CO 2 , using crushed rock.…”
Section: Background On Mineral Carbonation Experiments and Testsmentioning
confidence: 99%